Sorafenib: 10 years after the first pivotal trial. (July 2015) - Gadaleta-Caldarola, Gennaro; Infusino, Stefania; Divella, Rosa; Ferraro, Emanuela; Mazzocca, Antonio; De Rose, Ferruccio; Filippelli, Gianfranco; Abbate, Ines; Brandi, Mario
ABSTRACT : Sorafenib is an oral multikinase inhibitor with anticancer activity against a wide spectrum of cancers. It is currently approved for the treatment of patients with hepatocellular carcinoma, advanced renal cell carcinoma or progressive, locally advanced or metastatic differentiated thyroid carcinoma. In this review, we present a number of studies that investigated the efficacy and safety of sorafenib in these settings. We also discuss the perspectives on the use of this molecule, including the role of sorafenib as comparator for the development of new drugs, the combination of sorafenib with additional therapies (such as transarterial chemoembolization for hepatocellular carcinoma) and the use of this treatment in several other advanced refractory solid tumors.